Pollen evidence for climatic variability and cultural disturbance in the Maya lowlands - Leyden, B.W.
Palynology provides a record of past environmental change in the Maya Lowlands. The underlying principles are simple, but, as with all proxies, there are limitations. During the late glacial period, environmental change was governed by climate, which was cooler and much drier and supported sparse temperate vegetation. The early Holocene epoch was warmer and very wet in the southern Lowlands when mesic tropical forests predominated, while the northern Yucatan Peninsula was edaphically dry until eustatic sea level rose. The modern distributions of plant associations and climatic gradients were established at the end of the early Holocene. Climatic variability continued throughout the Holocene. However, the ability of palynology to identify climatic events is hindered after the Maya became numerous in the Lowlands. Then, multidisciplinary studies provide a better interpretation of events, especially during the late Holocene. Pollen records poorly reflect cyclical droughts seen in isotopic records, as natural vegetation has adapted to these fluctuations.